2022
DOI: 10.1007/978-3-030-87664-7_21
|View full text |Cite|
|
Sign up to set email alerts
|

Future Trends in Digital Face Manipulation and Detection

Abstract: Recently, digital face manipulation and its detection have sparked large interest in industry and academia around the world. Numerous approaches have been proposed in the literature to create realistic face manipulations, such as DeepFakes and face morphs. To the human eye manipulated images and videos can be almost indistinguishable from real content. Although impressive progress has been reported in the automatic detection of such face manipulations, this research field is often considered to be a cat and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…For future work, the authors of [10] suggested the use of unsupervised or semi-supervised learning to improve the performance in terms of time and manual annotation processes. In [48], the authors highlighted the challenges and limitations that should be taken in consideration in the future researches. They described the work in this field as "a cat and mouse game"; whereas the detection techniques are improved, the manipulation methods are improved.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For future work, the authors of [10] suggested the use of unsupervised or semi-supervised learning to improve the performance in terms of time and manual annotation processes. In [48], the authors highlighted the challenges and limitations that should be taken in consideration in the future researches. They described the work in this field as "a cat and mouse game"; whereas the detection techniques are improved, the manipulation methods are improved.…”
Section: Introductionmentioning
confidence: 99%
“…They described the work in this field as "a cat and mouse game"; whereas the detection techniques are improved, the manipulation methods are improved. Many researches have been introduced tackling the manipulation detection issue; however, to the current date, there is no global reliable face manipulation detection technique, which means this field is still nascent [48][49][50]. One of the limitations that have been mentioned in [48] is the low detection accuracy in the GAN-based methods [51][52][53][54] when bad-quality input images are tested such as images in bad lighting conditions, noisy, blurry, and other low-resolution images.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even recent advances in inpainting methods show that they can fill large missing areas with meaningful structures and objects that do not exist anywhere else in the image [9]. Such advancements make the manipulation detection a very challenging process [13], especially when the aim is not only to discriminate manipulated images from the authentic ones, but also to pinpoint tampered regions at the pixel level [14]. Notably, different categories of GAN-based inpainting methods [15] are trained using various sizes of masks which enable them to predict small or large masked regions, leading to, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%